Cerebral Circulation and Metabolism 1975
DOI: 10.1007/978-3-642-65814-3_1
|View full text |Cite
|
Sign up to set email alerts
|

The Lower and Upper Limits for Autoregulation of Cerebral Blood Flow

Abstract: The existence of a lower blood pressure limit for autoregulation has been recognized since 1959 (9). A shift upward of the lower end of the autoregulation curve in chronic arterial hypertension was suggested by Gottstein (6) on the basis of data from the literature, but has never been demonstrated in the individual patient. The existence of an upper blood pressure limit for autoregulation was demonstrated by Ekstrom-Jodal et al. (4) in hypercapnic dogs, but was not found at normocapnia. The present communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…7 These are due to irregularities in the auto regulation of cerebral circulation. 8 Disruption of the blood-brain barrier occurs due to both the hypertension-induced capillary damage and the immune-mediated endothelial dysfunction. This leads to extravasations of red cells and plasma proteins into perivascular space causing cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
“…7 These are due to irregularities in the auto regulation of cerebral circulation. 8 Disruption of the blood-brain barrier occurs due to both the hypertension-induced capillary damage and the immune-mediated endothelial dysfunction. This leads to extravasations of red cells and plasma proteins into perivascular space causing cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
“…the relation between PP and CBF, is influenced by several factors. In hypertensive subjects, animal as well as human studies have shown a shift of the autoregulation curve to the right, with an increase in the upper and lower points of autoregulation ( JOHANSSON 1975, JONES et al 1975, STRANDGAARD et al 1975a).…”
Section: Discussionmentioning
confidence: 99%
“…Below this level of MABP the CBF will decrease. An upper limit of autoregulation has been found in animal experiments (EKSTROM-JODAL et al 1972), and was recently demonstrated in human studies (STRANDGAARD et al 1975a). False autoregulation and paradoxical CBF reactions to blood-pressure changes have been described in human studies of cerebral tumours (PALVOLGYI 1969) and apoplexy (PAULSON et al 1970).…”
mentioning
confidence: 87%
“…Also, cerebral blood flow in man does not change significantly as arterial pressure is lowered from 130 to 60 mm Hg. 24 The latter finding requires that total vascular resistance in this bed falls by half as arterial pressure is reduced. Since capillary and venous vessels do not participate in the response, precapillary resistance must fall by more than half.…”
mentioning
confidence: 99%